Impact of the change of copay policy in Medicare Part D on zoster vaccine uptake among Medicare beneficiaries in a managed care organization - Hechter, Rulin C. (BMC Health Serv Res, 2017)
BACKGROUND: Kaiser Permanente Southern California (KPSC) adopted the Medicare Part D Tier-6 with zero patient copay for zoster vaccination in 2012. We assessed the impact of the implementation on zoster vaccination rate (GSK study identifier: HO-13-14,182). METHODS: Zoster vaccination rate was examined among an open cohort of ≥65-year-old Medicare Part D beneficiaries during 01/01/2008–06/30/2014, compared to ≥65-year-old commercial health plan members and 60–64-year-old members. The demographics, vaccination records, and insurance and benefit type were confirmed through KPSC electronic medical record databases. Person-time based vaccination rate was calculated for each observation interval (calendar month or year). The changes in annual rates in one year pre- (2011) and post- (2012) Tier-6 implementation were compared in a difference-in-difference analysis. Linear spline Poisson regression models were fitted to compare the secular trend of monthly rates during pre and post Tier-6 implementation (01/2012). RESULTS: Zoster vaccination rate increased in Medicare Part D beneficiaries after the implementation of zero copay. The increase in annual vaccination rate from 2011 to 2012 was marginally higher in Medicare Part D beneficiaries but not statistically significant (difference in rate ratio [RR] = 0.04, p > 0.05) compared to commercial health plan members. Among non-Hispanic white members, the difference of RR was 0.09 (p = 0.020) between Medicare Part D beneficiaries and ≥65-year-old commercial plan members, and it was 0.08 (p = 0.034) compared to 60–64-year-old commercial plan members. In secular trend analysis, we did not observe significant increase in overall and race stratified zoster vaccination rate attributable to the implementation of the Tier-6. CONCLUSIONS: The impact of Tier-6 on zoster vaccination was not substantial in elderly Medicare Part D beneficiaries in this population where a lower than average copay ($20 to $40) was applied prior to the Tier-6 implementation. Further research is necessary to explore the numerical relationship between vaccination and amount of copay. TRIAL REGISTRATION: GSK study identifier: HO-13-14,182. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-2441-7) contains supplementary material, which is available to authorized users.